2016
DOI: 10.5958/2394-6776.2016.00027.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of postmortem findings of asphyxial deaths due to Hanging in urban region of Karnataka

Abstract: Hanging, a form of deliberate self-harm accounts for a large proportion of autopsies which forensic experts come across in their clinical tenure at various hospitals in almost all parts of India. A retrospective study was conducted in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…In the USA, firearms are used in most suicides, with risk of their use being highest where guns are kept in households. 16 In majority of the 167 (81.46%) cases both in male and female the position of ligature mark was situated above thyroid cartilage and hyoid bone which is similar with the findings of Dekal RV & Shruthi P. 17 In our present study, single turn ligature mark was seen in maximum number of cases i.e, 189 (92.19%) which is consistent with finding of Arif M et al 18 It may be due to the fact that most victims used limited length of household available ligature material. Hanging deaths with three or more turns marks was observed more in male i.e, 1.47% than in female (0.97%).…”
Section: Discussionsupporting
confidence: 82%
“…In the USA, firearms are used in most suicides, with risk of their use being highest where guns are kept in households. 16 In majority of the 167 (81.46%) cases both in male and female the position of ligature mark was situated above thyroid cartilage and hyoid bone which is similar with the findings of Dekal RV & Shruthi P. 17 In our present study, single turn ligature mark was seen in maximum number of cases i.e, 189 (92.19%) which is consistent with finding of Arif M et al 18 It may be due to the fact that most victims used limited length of household available ligature material. Hanging deaths with three or more turns marks was observed more in male i.e, 1.47% than in female (0.97%).…”
Section: Discussionsupporting
confidence: 82%
“…Two-year study by Dekal V, Shruthi P shows the incidence rate of hanging rate 27.9% of total autopsies. 4 10 Study which found similar evidence of common position of knot on right side of the neck. However, Ambade VN, Tumram N et al study 8 reveals the most common position of the knot was on the left side of the neck.…”
Section: Discussionmentioning
confidence: 74%
“…Our results are similar with the study conducted by Dekal V it was observed that in 192 (84.95%) cases, the level of ligature mark was above the level of thyroid cartilage. 9 Out of 50 cases of hanging, fracture of hyoid bone present in 1 (2%) case.…”
Section: Discussionmentioning
confidence: 96%